The effect of interdisciplinary treatment on sickness absence and disability pension among chronic pain patients on partial disability pension - Constan, Lea; Frumento, Paolo; LoMartire, Riccardo (PloS one, 2025)
Studies evaluating the effects of interdisciplinary treatment (IDT) on sickness absence and disability pension (SA/DP) have yielded contradictory findings. Evidence indicates that positive treatment effects are restricted to patients with a poor SA/DP prognosis. This study therefore analyzed the effect of IDT in working age patients on partial disability pension, which is a group with a particularly poor prognosis. With data from 479 patients on partial disability pension, this register-based cohort study compared the effects of IDT to those of unspecified interventions. We considered two response variables: total net SA/DP days across the span of three years from the first visit to a Swedish specialist pain clinic, and the risk of having the maximum possible 1096 SA/DP days over the same period. Our results showed that both the total net SA/DP days (mean difference: 11; 95% confidence interval: -30 to 51) and the risk of 1096 SA/DP days (risk ratio: 1.0; 95% confidence interval: 0.6 to 1.4) were similar irrespective of intervention type. Under our theoretical model, we thereby found no support in favor of IDT over less intensive interventions in working age patients with partial DP. This raises questions about the specific criteria under which IDT proves effective.